1992
DOI: 10.1128/aac.36.7.1519
|View full text |Cite
|
Sign up to set email alerts
|

Didanosine pharmacokinetics in patients with normal and impaired renal function: influence of hemodialysis

Abstract: The pharmacokinetics of didanosine were investigated following oral administration of a single 375-mg dose to eight human immunodeficiency virus-seropositive patients with normal renal function and eight human immunodeficiency virus-seropositive uremic patients. In uremic patients, the plasma half-life was longer than that in control patients (respectively, 4.5 +/- 2.2 and 1.6 +/- 0.4 h). The ratio of total plasma clearance to absolute bioavailability was four- to fivefold lower in uremic patients than in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…The total clearance of ddI after oral administration, both antepartum ( mL/min or 2364 ‫ע‬ 1064 mL/min/kg) and postpartum ( mL/min 30. 2 ‫ע‬ 19.4 2517 ‫ע‬ 1879 or mL/min/kg), is similar to those obtained by oth-38.0 ‫ע‬ 36.2 ers in adult male and nonpregnant female subjects (2660 ‫ע‬ mL/min [22]; mL/min/kg [23]). In addition, 1297 36.4 ‫ע‬ 11.0 the bioavailability of ddI in the study's pregnant women (54%) is similar to that published earlier in nonpregnant subjects with different formulations (∼41% [24]; ∼43% [17]).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The total clearance of ddI after oral administration, both antepartum ( mL/min or 2364 ‫ע‬ 1064 mL/min/kg) and postpartum ( mL/min 30. 2 ‫ע‬ 19.4 2517 ‫ע‬ 1879 or mL/min/kg), is similar to those obtained by oth-38.0 ‫ע‬ 36.2 ers in adult male and nonpregnant female subjects (2660 ‫ע‬ mL/min [22]; mL/min/kg [23]). In addition, 1297 36.4 ‫ע‬ 11.0 the bioavailability of ddI in the study's pregnant women (54%) is similar to that published earlier in nonpregnant subjects with different formulations (∼41% [24]; ∼43% [17]).…”
Section: Discussionsupporting
confidence: 83%
“…Additional infants need to be studied to make these comparisons. An investigation by Gibb et al [25] in 8 male HIV-infected children (aged 3-14 years) found that the plasma half-life of ddI was h and the oral clearance of the drug (100 0.9 ‫ע‬ 0.3 mg/m 2 ) was mL/min/kg, a value almost double that 71.1 ‫ע‬ 59.9 observed in adult subjects (table 2) [23]. However, when the value of oral clearance of ddI is normalized to body surface area, the oral clearance of ddI in the Gibb study (1195 mL/ min/m 2 ) is very close to the clearance in the postpartum women ( mL/min/m 2 ).…”
Section: Discussionmentioning
confidence: 88%
“…As expected, didanosine clearance is reduced in patients with renal dysfunction [41]. Haemodialysis removes didanosine from plasma, although a 4 h dialysis removes only 20% of the didanosine dose.…”
Section: Metabolism and Excretionsupporting
confidence: 73%
“…Ribavirin partitions widely into the tissue, with a high apparent volume of distribution [3]; thus, hemodialysis would not be expected to remove significant quantities of the drug. Low or minimal hemodialysis clearance has also been reported for other nucleoside analogs (didanosine [9] and zidovudine [10]). …”
Section: Discussionmentioning
confidence: 91%
“…Patients with chronic renal dysfunction appear to be more susceptible to anemia in the presence of ribavirin than normal subjects [9]. As well as ribavirin-induced hemolysis, other contributory factors may include inadequate marrow responsiveness to anemia, and reduced erythrocyte longevity due to uremia.…”
Section: Discussionmentioning
confidence: 98%